2020
DOI: 10.1002/bdr2.1742
|View full text |Cite
|
Sign up to set email alerts
|

Developmental 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin exposure of either parent enhances the risk of necrotizing enterocolitis in neonatal mice

Abstract: Background: Necrotizing enterocolitis (NEC) is a rare, but potentially fatal intestinal inflammatory condition most often arising in premature infants. Infants provided formula are also at greater risk of developing this disease. Although the majority of formula-fed, preterm infants do not develop NEC, up to 30% of infants with the disease do not survive. Thus, identifying additional, currently unrecognized factors, which may predispose a specific infant to NEC development would be a significant clinical advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…Several studies have suggested that placental dysfunction precedes (and contributes to) the development of new BPD [21][22][23][24]. The onset and severity of developmental lung diseases, such as new BPD, have also been linked to exposure to pollution in humans and experimental animal models [25][26][27][28][29]. Our laboratory found that the offspring of male mice that were exposed to TCDD in utero were also susceptible to new BPD [29].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Several studies have suggested that placental dysfunction precedes (and contributes to) the development of new BPD [21][22][23][24]. The onset and severity of developmental lung diseases, such as new BPD, have also been linked to exposure to pollution in humans and experimental animal models [25][26][27][28][29]. Our laboratory found that the offspring of male mice that were exposed to TCDD in utero were also susceptible to new BPD [29].…”
Section: Introductionmentioning
confidence: 79%
“…To assess the development of new BPD, we performed necropsies on PND 11 as our previous studies revealed that the disease was prevalent by this time in F2TCDD pups [29]. On PND 11 at 1100 h local time, CT and F2TCDD pups were weighed and observed for external signs of new BPD (labored breathing and/or delayed growth), then euthanized by decapitation performed under deep anesthesia as per the AAALAC guidelines.…”
Section: Euthanasia and Collection Of Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exogenous AhR agonists can affect intestinal homeostasis and impact gastrointestinal diseases. Mokshagundam et al ( 50 ) demonstrated that in utero exposure to the environmental toxin 2,3,7,8-tetrachlorodibenzo- p -dioxin, a potent AhR agonist, promoted the development of NEC. In contrast, exogenous dietary AhR proligands, such as I3C, influence the postnatal expansion of intestinal innate lymphoid cells to protect against intestinal infections ( 11 , 39 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated NEC incidence ranges from 0.3 to 2.4 infants per 1000 live births, accounting for approximately 7%-11% of neonates weighing < 1,500 g [ 1 ]. Unfortunately, the survival rate of NEC infants with birth weights less than 1,500 g is only approximately 70% [ 4 ]. Moreover, 25% of NEC infants develop short bowel syndrome (SBS) and neurodevelopmental disorders (NDs) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%